Optimization of therapeutic strategies for selective lateral lymph node dissection after neoadjuvant chemoradiotherapy in patients with rectal cancer with clinical suspected lateral lymph node metastasis - Liu, Yuan; Bao, Mandoula; Jiang, Yujuan; Li, Feng; Xing, Wei; Yang, Zhufeng; Liu, Qian (Frontiers in Oncology, 2023)
Background Selective lateral lymph node (LLN) dissection with total mesorectal excision after neoadjuvant chemoradiotherapy (nCRT) is pointed out to reduce lateral compartment recurrence and to improve survival in patients with rectal cancer with LLN metastases. This study aimed to explore the safety, surgical indications, and survival outcomes of LLN dissection after nCRT. Methods This multicenter retrospective study included patients with rectal cancer with clinical evidence of LLN metastases (n = 466) treated across three hospitals in China. Patients who underwent total mesorectal excision and LLN dissection were grouped into nCRT (n = 155) and non-nCRT (n = 291), respectively. Propensity score matching was used to minimize selection bias. Results After matching, nCRT did not significantly increase the surgery duration, intraoperative blood loss or postoperative complications (P > 0.05). In a multivariate logistic regression analysis, poor/mucinous/signet adenocarcinoma (P = 0.042) and post-nCRT LLN short diameter ≥7 mm (P < 0.001) were independent risk factors for pathological LLN metastasis after nCRT. Overall survival (P < 0.001) and disease-free survival (P < 0.001) were significantly worse in patients with LLN metastasis, which was, however, not an independent risk factor for survival after eliminating confounders. Multivariate prognostic analysis of 40-patient subset with pathological LLN metastasis showed that distant metastasis, metastasis beyond the obturator or internal iliac region, and ≥2 LLN metastasis were independent predictors of poor overall survival. Conclusions Selective LLN dissection after nCRT is safe and feasible with acceptable perioperative outcomes. Patients with a post-nCRT LLN short diameter ≥7 mm or poor/mucinous/signet adenocarcinoma should receive supplementary LLN dissection after nCRT. However, patients with distant metastasis, metastasis beyond the obturator or internal iliac region, and involvement of ≥2 LLN may not benefit from LLN dissection, and LLN dissection should be carefully considered in such patients.